Multi-Site Adult Drug Court Evaluation (MADCE), 2003-2009 - Rossman, Shelli B. ([Verlag nicht ermittelbar], 2012)
The Multi-Site Adult Drug Court Evaluation (MADCE) study included 23 drug courts and 6 comparison sites selected from 8 states across the country. The purpose of the study was to: (1) Test whether drug courts reduce drug use, crime, and multiple other problems associated with drug abuse, in comparision with similar offenders not exposed to drug courts, (2) address how drug courts work and for whom by isolating key individual and program factors that make drug courts more or less effective in achieving their desired outcomes, (3) explain how offender attitudes and behaviors change when they are exposed to drug courts and how these changes help explain the effectiveness of drug court programs, and (4) examine whether drug courts generate cost savings. Offenders in all 29 sites were surveyed in 3 waves, at baseline, 6 months later, and 18 months after enrollment. The research comprises three major components: process evaluation, impact evaluation, and a cost-benefit analysis. The process evaluation describes how the 23 drug court sites vary in program eligibility, supervision, treatment, team collaboration, and other key policies and practices. The impact evaluation examines whether drug courts produce better outcomes than comparison sites and tests which court policies and offender attitudes might explain those effects. The cost-benefit analysis evaluates drug court costs and benefits.